OCCURRENCE OF THE THREE SPOT GOURAMI Trichopodus trichopterus (ACTINOPTERYGII: OSPHRONEMIDAE) IN GUANABARA BAY, SOUTHEASTERN BRAZIL - Cavalcanti, Mauro José; Lopes, Paulo Roberto Duarte (Arquivos de Ciências do Mar, 2017)
The Spot gourami Trichopodus trichopterus is recorded for the first time in mangrove environments from Porto do Rosa, São Gonçalo (22º47´S - 43º02´W), eastern Guanabara Bay, Rio de Janeiro state, Brazil. The species is seemingly established in the area, where it may have been introduced by aquarium trade activities. The potential environmental impacts of this introduction to the local ecosystem, already under stress by pollution and habitat destruction, are discussed.